Work Stress Among Nigerian Electronic Technology Teachers: Exploring its Influence on Job Performance with Stress Beliefs as Moderator (Asean Journal of Engineering Education, 2023)
Electronic technology teachers are among professionals who may face adverse effects of stress due to the nature of their job. This study explores the relationship between work stress and job performance among electronic technology teachers and investigates the role of stress beliefs in moderating this relationship. Purposive sampling was used to select 123 electronic technology teachers and 22 heads of departments in government-owned universities in Nigeria, who provided data for the study. Results indicate that work stress significantly predicts job performance among electronic technology teachers (β = .60, p < .001). Additionally, stress beliefs were found to be a significant predictor of job performance (β = .61, p < .001). Furthermore, stress beliefs were found to moderate the relationship between work stress and job performance. The findings suggest that teachers' job performance is influenced by both work stress and stress beliefs. Positive stress beliefs are associated with improved job performance, while negative stress beliefs may lead to decrements in performance. Understanding the interplay between work stress, stress beliefs, and job performance can inform interventions to improve the performance of electronic technology teachers and, subsequently, the skill acquisition of their students.
Keywords: Electronic Technology Teachers; Work Stress; Job Performance; Stress Beliefs